Outcomes of SARS-CoV-2 infection among children and young people with pre-existing rheumatic and musculoskeletal diseases. Issue 7 (25th March 2022) - Kearsley-Fleet, Lianne; Chang, Min-Lee; Lawson-Tovey, Saskia; Costello, Ruth; Fingerhutová, Šárka; Švestková, Natálie; Belot, Alexandre; Aeschlimann, Florence A; Melki, Isabelle; Koné-Paut, Isabelle; Eulert, Sascha; Kallinich, Tilmann; et al.
Abstract : Objectives: Some adults with rheumatic and musculoskeletal diseases (RMDs) are at increased risk of COVID-19-related death. Excluding post-COVID-19 multisystem inflammatory syndrome of children, children and young people (CYP) are overall less prone to severe COVID-19 and most experience a mild or asymptomatic course. However, it is unknown if CYP with RMDs are more likely to have more severe COVID-19. This analysis aims to describe outcomes among CYP with underlying RMDs with COVID-19. Methods: Using the European Alliance of Associations for Rheumatology COVID-19 Registry, the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Registry, and the CARRA-sponsored COVID-19 Global Paediatric Rheumatology Database, we obtained data on CYP with RMDs who reported SARS-CoV-2 infection (presumptive or confirmed). Patient characteristics and illness severity were described, and factors associated with COVID-19 hospitalisation were investigated. Results: 607 CYP with RMDs <19 years old from 25 different countries with SARS-CoV-2 infection were included, the majority with juvenile idiopathic arthritis (JIA; n=378; 62%). Forty-three (7%) patients were hospitalised; three of these patients died. Compared with JIA, diagnosis of systemic lupus erythematosus, mixed connective tissue disease, vasculitis, or other RMD (OR 4.3; 95% CI 1.7 to 11) or autoinflammatory syndrome (OR 3.0; 95% CI 1.1 to 8.6) was associated with hospitalisation, as was obesity (OR 4.0; 95% CI 1.3 to 12). Conclusions: This is the most significant investigation to date of COVID-19 in CYP with RMDs. It is important to note that the majority of CYP were not hospitalised, although those with severe systemic RMDs and obesity were more likely to be hospitalised.